Occupational physical activity: the good, the bad, and the proinflammatory - Jordakieva, Galateja; Hasenoehrl, Timothy; Steiner, Margarete; Jensen-Jarolim, Erika; Crevenna, Richard (Frontiers in Medicine, 2023)
Background Physical activity (PA) is beneficial for preventing several conditions associated with underlying chronic inflammation, e. g., cardiovascular disease (CVD) and cancer. While an active lifestyle appears to have anti-inflammatory effects, high levels of occupational PA (OPA) were associated with inflammation and elevated mortality risks. We aimed to summarize the current knowledge (1) on the association between inflammation and OPA and (2) its implications for health and mortality. Methods and results This mini-review summarized relevant literature published before January 2023 using established scientific databases and sources. For the primary outcome, observational studies (S) reporting immunological effects (O) in subjects (P), with high (I) vs. low OPA (C), were included. For secondary outcomes, i.e., morbidity and mortality associated with inflammatory processes, (systematic) reviews were included. While “active” occupations and “moderate” OPA appear to have beneficial effects, low (particularly sedentary) and “high-intensity” OPA (particularly including heavy lifting tasks) were associated with inflammation and (CVD and cancer-related) mortality; higher leisure-time PA has been almost consistently associated with lower proinflammatory markers and all-cause mortality risks. Workplace interventions appear to counter some of the observed health effects of unfavorable work strain. Conclusion The few studies addressing OPA “intensity” and inflammatory markers are largely heterogeneous regarding OPA classification and confounder control. Sedentary and “heavy” OPA appear to promote proinflammatory effects. In addition to targeted management of work-related physical strain and hazardous environmental co-factors, occupational health providers should focus on employer-initiated exercise interventions and the promotion of leisure-time PA.